Online social support groups for informal caregivers of hospice patients with cancer. (February 2020) - Benson, Jacquelyn J.; Oliver, Debra Parker; Washington, Karla T.; Rolbiecki, Abigail J.; Lombardo, Cynthia B.; Garza, Julia E.; Demiris, George
Abstract: Purpose: Social support is an important factor in reducing caregiver burden, however, accessing social support via traditional means is often challenging for family caregivers of hospice patients. Online support groups may offer an effective solution. The present study sought to understand dynamics of online social support among family and other informal (e.g., friends) caregivers of hospice cancer patients in an online social support group. The primary aim of the study was to identify types of online social support and support-seeking behaviors, with a secondary aim to understand informal hospice caregivers' preferences for social support. Method: Data used in this study were collected as part of a federally funded randomized clinical trial of an informal hospice cancer caregiver support intervention. Findings are based on directed and conventional content analysis of support group members' posts and comments—including text and images—and a sample of caregivers' exit interviews. Results: Analyses demonstrated that the majority of online support provided by group members was emotional support, followed by companionship support, appraisal support, and informational support. Instrumental support was rarely provided. Support was primarily elicited in an indirect manner through self-disclosure and patient updates, with few overt requests for support. Conclusions: Findings suggest online social support groups can be a valuable resource for informal caregivers who are in need of emotional support and lack the ability to access face-to-face support groups. Clinical implications of this research to healthcare systems regarding the importance of incorporating nurses and other medical professionals as co-facilitators of online support groups are discussed. Highlights: Informal hospice caregivers of cancer patients utilized online support groups (OSGs) primarily to exchange emotional support. Informal hospice caregivers of cancer patients mainly elicited support online by self-disclosing, or providing patient updates. Informal hospice caregivers of cancer patients requested additional informational, companionship, and appraisal support. Nurses as facilitators of OSGs may bolster provision of informational support and ensure accuracy of information provided.